Kajian Reservoir Leptospira di Daerah Sporadis Leptospirosis - Dewi Puspita Ningsih; Zumrotus Sholichah (Media Kesehatan Masyarakat Indonesia, 2018)
Districts in Central Java have been reported as leptospirosis area, one of them is Purworejo. Leptospirosishas been reported in Purworejo since 2005, but less information and reports on rats species and leptospirapresence in rats and shrews. This study aims to examine reservoir of leptospira and describe infected serovar inPurworejo.This research was carried out in the Bendosari village Gebang subdistrit, on May until June 2011, andcross sectional study. Data collected by catching and continued by examination of leptospira with MAT. The resultshown, that total of rats and shrew were recorded for 30. The most rats and shrew prevalence were recorded about66,67% of Rattus tanezumi species, catched in house was about 66,67% with female was about 60%. The resultof MAT as much 30% rats and shrews infected leptospira with titer >1:40 and infected serovar are L. sarmin, L.semaranga, L. javanica, L. icterohaemorrhagie, L. Patoc and L. Sejroe. House rats and shrews has potentiallytransmited Leptospira in human.